Foreigner and Domestic Tourism: The Attractiveness of Italian Provinces - Ferri, Valentina; Lollo, Giuseppe (Mediterranean Journal of Social Sciences, 2012)
Tourist arrivals, in Italy, are concentrated in areas where cultural and natural heritage is associated to the organization ofterritories, equipped areas and services. In particular these issues are important for foreigners tourists who need a lot of services tospend a good period. In this work we aims to analyze the characteristics of Italian provinces and the capacity of attractiveness of theseterritories; on this way, to analyze the touristic flow in Italian provinces, first of all we have individuated the ten best performances ofitalian provinces with respect to domestic and international tourist arrivals and permanence during the year 2008. We intend to deepenthe relationships of the most important component in these four groups with the best performances of attraction (best performance ofdomestic tourism in terms of arrivals and permanence; best performance of foreigners tourists in terms of arrivals and permanence).Through four principal component analysis we have analyzed the key variables for each group: infrastructure, transports, hotels, otherstructures able to receive the tourists, restaurants, cultural and naturalistic heritage (museums, UNESCO sites, parks), organization ofevents, entertainments (sport, disco etc). With this methodology emerges that in some cases, the organization of territories, thepresence of adequate structure and infrastructure is more important than the presence of significant cultural and natural sites. Thesources of data are the National Institute for Statistics (ISTAT), United Nations Educational, Scientific and Cultural Organization(UNESCO), Trail and Ministry of Infrastructure and Transportation and Italian Authors and Publishers Association (SIAE).